Agrobacterium tumefaciens - mediated transformation of nicotiana benthamiana with dehalogenase gene resistant to monochloroacetic acid - Mohamed, Elizah (2017)
Weeds give adverse effects to crops because of the competition to get nutrients, light and moisture. Many farmers used broad-spectrum herbicide such as monocloroacetic acid (MCA) which is effective at killing a wide range of weeds. Unfortunately, broad-spectrum of herbicide can also kill valuable crops and cause significant losses in agricultural productivity. One of the solutions to this problem is by developing herbicide resistant plant using dehalogenase D (dehD) gene isolated from Rhizobium sp. RC1. A dehD gene encoding dehalogenase enzyme that has the capability to degrade monochloroacetic acid (MCA) was isolated and characterized from Rhizobium sp. RC1. dehD gene was used as herbicide resistance gene and selectable marker gene in Nicotiana benthamiana plant transformation. The 798 bp dehD gene was inserted into pCAMBIA 1305.2 under the control of the Cauliflower Mosaic Virus 35S (CaMV35S) promoter and designated as pCAMdehD, with a total size of 10,592 bp. A few parameters of Agrobacterium tumefaciens-mediated transformation were optimized including hygromycin concentration (40 μg/mL of hygromycin), and the MCA toxicity level to N. benthamiana at tissue culture (60 μg/L of MCA) and whole plant stage (2.0 g/L of MCA). pCAMdehD was introduced into N. benthamiana via Agrobacterium mediated transformation method. Based on the screening of the transformants on MS media containing 60 μg/L MCA, the results showed that N. benthamiana was successfully transformed with dehalogenase D gene with 50 % of transformation efficiency. The integration and expression of dehD gene in N. benthamiana were confirmed by PCR, Southern Blotting and reverse transcription PCR. Analysis of leaf-painting assay revealed that transgenic N. benthamiana (T1) was resistant to 4.0 g/L MCA compared to 2.0 g/L for non-transformed plants control. The Chi Square analyses of five transgenic plants (T1), suggested that the dehD gene was segregated according to Mendelian 3:1 ratio. These findings showed that transgenic N. benthamiana plant resistant to MCA herbicide was successfully produced.